Pathways to Homelessness - Using linked data to inform homelessness prevention services - Dixie, Laura (International Journal of Population Data Science, 2026)
Homelessness is a significant and growing problem in Australia. People who are experiencing homelessness are more likely to have other vulnerabilities including low incomes, ill mental health or experiences of domestic violence. However, the understanding of how homelessness services fit into the broader picture of government support for vulnerable people had been largely unexplored. To address this, the New South Wales government engaged us to undertake a linked data research project, aiming to gain a comprehensive understanding of homelessness. We completed a research project that delivered: A bespoke linked dataset covering a large population across multiple sectors Analysis of government service use and associated costs to inform investment in prevention programs Predictive models identifying key risk factors to support early identification of groups at higher risk of homelessness. The linked dataset created for this project was one of the most comprehensive datasets related to homelessness in Australia, covering over 625,000 people across 19 government services. The study population was formed using a case and comparison design. The dataset is large enough to be able to meaningfully analyse homelessness risk across the population. This is in contrast to other research which tends to consider small cohorts who all have experiences of homelessness, and so there is no ability to provide comparisons to a baseline. This presentation will cover the value of linked government data and the rich picture it can provide.